Acute Low-Volume High-Intensity Interval Exercise and Continuous Moderate-Intensity Exercise Elicit a Similar Improvement in 24-h Glycemic Control in Overweight and Obese Adults - Parker, Lewan; Shaw, Christopher S.; Banting, Lauren; Levinger, Itamar; Hill, Karen M.; McAinch, Andrew J.; Stepto, Nigel K. (Frontiers in Physiology, 2017)
Background: Acute exercise reduces postprandial oxidative stress and glycemia; however, the effects of exercise intensity are unclear. We investigated the effect of acute low-volume high-intensity interval-exercise (LV-HIIE) and continuous moderate-intensity exercise (CMIE) on glycemic control and oxidative stress in overweight and obese, inactive adults. Methods: Twenty-seven adults were randomly allocated to perform a single session of LV-HIIE (9 females, 5 males; age: 30 ± 1 years; BMI: 29 ± 1 kg·m−2; mean ± SEM) or CMIE (8 females, 5 males; age: 30 ± 2.0; BMI: 30 ± 2.0) 1 h after consumption of a standard breakfast. Plasma redox status, glucose and insulin were measured. Continuous glucose monitoring (CGM) was conducted during the 24-h period before (rest day) and after exercise (exercise day). Results: Plasma thiobarbituric acid reactive substances (TBARS; 29 ±13%, p < 0.01; mean percent change ±90% confidence limit), hydrogen peroxide (44 ± 16%, p < 0.01), catalase activity (50 ± 16%, p < 0.01), and superoxide dismutase activity (21 ± 6%, p < 0.01) significantly increased 1 h after breakfast (prior to exercise) compared to baseline. Exercise significantly decreased postprandial glycaemia in whole blood (−6 ± 5%, p < 0.01), irrespective of the exercise protocol. Only CMIE significantly decreased postprandial TBARS (CMIE: −33 ± 8%, p < 0.01; LV-HIIE: 11 ± 22%, p = 0.34) and hydrogen peroxide (CMIE: −25 ± 15%, p = 0.04; LV-HIIE: 7 ± 26%; p = 0.37). Acute exercise provided a similar significant improvement in 24-h average glucose levels (−5 ± 2%, p < 0.01), hyperglycemic excursions (−37 ± 60%, p < 0.01), peak glucose concentrations (−8 ± 4%, p < 0.01), and the 2-h postprandial glucose response to dinner (−9 ± 4%, p < 0.01), irrespective of the exercise protocol. Conclusion: Despite elevated postprandial oxidative stress compared to CMIE, LV-HIIE is an equally effective exercise mode for improving 24-h glycemic control in overweight and obese adults.